Evaluation by Competences in Higher Education: Good Practices in the Face of Current Challenges - Elena Cano (Universidad Autónoma de Madrid, 2019)
The European Higher Education Area is developed, among other tools, from the design of the degrees based on the desired proficiency profiles for graduates. However, despite the fact that the Bologna process already has a long history (in 2019, 20 years of the Bologna Declaration have been completed) and despite the advances that have been taking place, the evaluation by competencies in the framework of Higher education still has some difficult challenges (Cano, 2016).